2018
DOI: 10.1002/biot.201800179
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Continuous Multicolumn Chromatography Enables Increased Productivities and Cost Savings by Employing More Columns

Abstract: The advantages of continuous chromatography with respect to increased capacity are well established. However, the impact of different loading scenarios and total number of columns on the process economics has not been addressed. Here four different continuous multicolumn chromatography (MCC) loading scenarios are evaluated for process performance and economics in the context of a Protein A mAb capture step. To do so, a computational chromatography model is validated experimentally. The model is then used to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
(31 reference statements)
0
16
0
Order By: Relevance
“…The biopharmaceutical industry is following other industries in moving from discrete batch operation to integrated continuous manufacturing, especially for high demand products, such as monoclonal antibodies (MAbs; Shukla, Wolfe, Mostafa, & Norman, 2017; Walsh, 2018). The drivers for continuous processing are many‐fold; process intensification and cost savings (Baur, Angarita, Müller‐Späth, Steinebach, & Morbidelli, 2016; Hummel et al, 2018; Pagkaliwangan, Hummel, Gjoka, Bisschops, & Schofield, 2018; Pollock, Coffman, Ho, & Farid, 2017) might emerge as the most obvious ones but steady‐state operation and thus better, more reproducible quality have also been associated with continuous biomanufacturing (Karst et al, 2017; Kaufman, Wasley, & Dorner, 1988; Walther et al, 2019). While upstream processing is ahead in this transition, where chemostat and perfusion reactors are commonly employed at the manufacturing scale (Arathoon & Birch, 1986; Shukla et al, 2017; Warnock & Al‐Rubeai, 2006), downstream operations have only in recent years started this transition.…”
Section: Introductionmentioning
confidence: 99%
“…The biopharmaceutical industry is following other industries in moving from discrete batch operation to integrated continuous manufacturing, especially for high demand products, such as monoclonal antibodies (MAbs; Shukla, Wolfe, Mostafa, & Norman, 2017; Walsh, 2018). The drivers for continuous processing are many‐fold; process intensification and cost savings (Baur, Angarita, Müller‐Späth, Steinebach, & Morbidelli, 2016; Hummel et al, 2018; Pagkaliwangan, Hummel, Gjoka, Bisschops, & Schofield, 2018; Pollock, Coffman, Ho, & Farid, 2017) might emerge as the most obvious ones but steady‐state operation and thus better, more reproducible quality have also been associated with continuous biomanufacturing (Karst et al, 2017; Kaufman, Wasley, & Dorner, 1988; Walther et al, 2019). While upstream processing is ahead in this transition, where chemostat and perfusion reactors are commonly employed at the manufacturing scale (Arathoon & Birch, 1986; Shukla et al, 2017; Warnock & Al‐Rubeai, 2006), downstream operations have only in recent years started this transition.…”
Section: Introductionmentioning
confidence: 99%
“…Many examples have been published to show this approach can increase resin utilization and increase productivity. This opens up the possibility to reduce the amount of resin required in a commercial bioprocess and improve manufacturing economics (Baur, Angarita, Müller‐Späth, Steinebach, & Morbidelli, ; Bisschops & Brower, ; Dutta, Tan, Napadensky, Zydney, & Shinkazh, ; Girard et al, ; Jagschies, ; Pagkaliwangan, Hummel, Gjoka, Bisschops, & Schofield, ; Warikoo et al, ; Xenopoulos, )…”
Section: Introductionmentioning
confidence: 99%
“…By operating many chromatography columns in a countercurrent or concurrent manner, continuous operation can be achieved, as the loading is carried out in the first column and all of the other steps (washing, elution, regeneration, and re-equilibration) in the subsequent ones (Jungbauer, 2013). Continuous annular chromatography (CAC), simulated moving bed (SMB) chromatography, countercurrent chromatography (CCC), multicolumn countercurrent solvent gradient purification chromatography (MCSGP), and countercurrent tangential (CCT) chromatography are used in the continuous mode of operation (Pagkaliwangan et al, 2018;Rathore et al, 2018;Vogg et al, 2018). Some of the commercially available continuous chromatography platforms are listed in Table 6.…”
Section: Continuous Chromatographymentioning
confidence: 99%
“…In a scale-up study for purification of mAbs, it was reported that buffer savings of around 50% were achieved using a PCC strategy (Angelo et al, 2018). Four different loading scenarios with a Cadence BioSMB MCC for the Protein A mAb capture step were evaluated, and it was concluded that by adding more columns, up to 65% more productivity (at feed concentrations of above 5 g/l) could be achieved (Pagkaliwangan et al, 2018). The effect of particle size (85 vs. 50 µm) on the performance of continuous capture Protein A affinity chromatography was studied with respect to feed titers, load flow rates, and target breakthrough with single column batch, two-column CaptureSMB, and four-column PCC using a DOE approach.…”
Section: Continuous Chromatographymentioning
confidence: 99%